2011
DOI: 10.1007/s10620-011-1902-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptors Attenuates Endotoxin-Induced Liver Injury in Mice with Nonalcoholic Fatty Liver Disease

Abstract: Activation of LXRs attenuates LPS-induced liver injury in murine NAFLD through inhibiting the pro-inflammatory activity of macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The hepatic TG disorder is a major health problem, and much attention has been paid on its pathogenesis and etiology [ 14 , 15 ]. The disorder can influence the liver function and animals’ growth.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic TG disorder is a major health problem, and much attention has been paid on its pathogenesis and etiology [ 14 , 15 ]. The disorder can influence the liver function and animals’ growth.…”
Section: Discussionmentioning
confidence: 99%
“…This study used low dose LPS (2 mg/kg, i.p. ), which has been previously shown to induce organ injury in lung [38] , kidney [39] and liver [40] . Here, we demonstrated that this low dose of LPS caused inflammation, neutrophil infiltration and histological evidence of tissue injury in lungs, liver and kidney ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The activation of LXR also inhibits the expression of TNF-a and iNOS in bone marrow-derived macrophages of mice in vitro. 52 Human hepatic expression of LXRa and its related lipogenic and inflammatory genes, such as TNF-a, IL-6, osteopontin, iNOS, COX-2 and the suppressor of cytokine signaling 3 protein is abnormally increased in NAFLD and hepatitis C patients with steatosis, confirmed a potential role of LXRa in the pathogenesis of hepatic steatosis in these chronic liver diseases. 53 These data indicate that the activation of LXRa is beneficial for hepatic inflammation in hepatic steatosis.…”
Section: Lxr and Nafldmentioning
confidence: 89%
“…T0901317 administration decreases hepatic TNF‐α and iNOS expression through inhibiting c‐Jun N‐terminal kinases and the phosphatidylinositol 3‐kinase signaling pathway in the liver. The activation of LXR also inhibits the expression of TNF‐α and iNOS in bone marrow‐derived macrophages of mice in vitro 52 . Human hepatic expression of LXRα and its related lipogenic and inflammatory genes, such as TNF‐α, IL‐6, osteopontin, iNOS, COX‐2 and the suppressor of cytokine signaling 3 protein is abnormally increased in NAFLD and hepatitis C patients with steatosis, confirmed a potential role of LXRα in the pathogenesis of hepatic steatosis in these chronic liver diseases 53 .…”
Section: Introductionmentioning
confidence: 99%